Perancangan Video Feature Perjalanan Biji Kopi sebagai Media Informasi Pengolahan Kopi - Septian Evan Prasetya (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2020)
Indonesian coffee is very popular in other countries. The uniqueness and the diversity of its taste make Indonesian coffee such a worldwide success. Not only that, but the coffee culture and coffee business in Indonesia also experienced a significant increase as well. However, there are some negative effects that emerged from this phenomenon. In fact, the quality of coffee in Indonesia has begun to decrease due to high coffee business competition. This makes coffee entrepreneurs prioritize the quantity over the quality of coffee to survive. Moreover, many people start a coffee business without proper knowledge about coffee itself. The main purpose of this design is to make a feature video about the coffee process, from harvesting to the brewing stage. The data collecting method used in this design is a qualitative descriptive method. And the design method used in this design is the video production method. From this design, Hopefully, the society can understand the process of coffee making, and interpret coffee as an art. The final result of this design is a feature video with a duration of 05:08 minutes, five series of teaser video with a duration of approximately 15-30 seconds, and one set of Perjalanan Biji Kopi photo essay book.